KAJIAN ETNOMATEMATIKA TERHADAP KONSEP MATEMATIS PADA DESAIN PERAHU DAN ALAT TANGKAP IKAN TRADISIONAL MASYARAKAT PESISIR BENGKULU - Frenski Dwisetyo Nurcahyati; Merlia Desika Tiana; Nur Lailatul Hasanah; Suci Oktari Pratami; Betti Dian Wahyuni (PT. Hasba Edukasi Mandiri, 2026)
This study aims to examine the mathematical concepts contained in the design of traditional fishing boats and fishing gear used by the coastal community of Bengkulu through an ethnomathematical approach. The study employed a qualitative descriptive research method. Data were collected through observations, interviews, and documentation involving traditional fishermen and community members who understand the process of making and using traditional boats and fishing gear. The results showed that various mathematical concepts are embedded in the design of traditional boats and fishing gear. Traditional boats demonstrate mathematical concepts such as three-dimensional geometry, symmetry, measurement, proportional relationships, and angles, which contribute to balance and efficiency when operating at sea. Meanwhile, traditional fishing gear, particularly fish traps (bubu), reflects concepts of three-dimensional geometry, weaving patterns, symmetry, and proportional measurements that support their functionality. These findings indicate that the coastal community of Bengkulu has applied mathematical concepts in cultural practices and daily activities, even without formally recognizing them as mathematics. This study is expected to contribute to the preservation of local culture and provide contextual mathematics learning resources that are closely related to students' environments.